A multi-country, randomized trial of three nutritional supplements on short-term and sustained anthropometric recovery in children 6–24 months of age with moderate wasting and acute illnesses: the NUTRIMAM study protocol - The NUTRIMAM Study Team (Trials)
Abstract Background Globally, moderate wasting affects approximately 33 million children. Complex bidirectional interactions exist between wasting and infection in children. Children who experience both conditions have an increased risk of adverse outcomes including progression to severe wasting and mortality. Breaking the cycle between moderate wasting and infection could help improve growth and survival in these children. The NUTRIMAM trial will aim to investigate the efficacy of a 12-week regimen of three different nutritional interventions in at-risk young children (i.e., children who are moderately wasted and have one/more acute infections) on anthropometric recovery. Further, the study will explore whether recovery can be sustained with a post-intervention package that includes counseling and food vouchers. Sustaining anthropometric recovery beyond supplement administration will have important implications for programs. Methods NUTRIMAM is a multi-country, multi-center individually randomized, open-label, trial in five countries including Bangladesh, India, Mali, Pakistan, and Tanzania. A total of 6360 moderately wasted children aged 6 to 24 months with acute illness will be enrolled at health centers. Children will be randomly allocated to receive one of three dietary supplements (locally available foods, ready-to-use supplementary foods, or microbiota-directed supplementary foods) for 12 weeks. Anthropometric recovery will be assessed over this period. Participants who recover will then be re-randomized to a post-recovery support intervention comprising either counseling and food vouchers or routine standard of care for recovered children for an additional 12 weeks to determine if this intervention facilitates sustained recovery at 24 weeks. Discussion Children who are moderately wasted and have an infection are at higher risk of adverse outcomes. There are very few clinical trials that have been performed among children with moderate wasting with infectious illnesses to investigate if it is possible to break the undernutrition–infection cycle and thereby reduce the risk of nutritional deterioration to severe wasting or mortality and decrease the risk of acute infections. The results of the trial are anticipated to fill important evidence gaps in feeding recommendations for moderately wasted children with acute illness as well as interventions to sustain anthropometric recovery in children beyond the period of the nutritional intervention. Trial registration ISRCTN registry, ISRCTN53213318 . Registered on April 03, 2023.